Osłabianie Nietzschego - Zawadzki, Andrzej (Przestrzenie Teorii, 2007)
The essay deals with Vattimo's interpretation of Nietzsche in the context of contemporary critical discussion concerning Nietzsche's heritage in the modern philosophy. In his early book II soggetto e la maschera. Nietzche e la problema della liberazione (1974) Vattimo tries to picture Nietzsche as a philosopher of emancipation, who announces both social liberation of humanity from political oppression and domination, and cultural liberation of the symbolical domain (values, symbols, senses) from metaphysics and its categories like substance, essence, stable, immutable being. In his later essays on Nietzsche, gathered in the volume entitled Dialogo eon Nietzsche, Vattimo concentrates on hermeneutical aspects of Nietzsche's philosophy and shows his influence on contemporary philosophical hermeneutics and theory of interpretation.